Distribution and Threat Assessment of an Endemic and Endangered Species Angelica glauca in High Ranges of Western Himalaya. Issue 4 (1st October 2020) - Singh, Gajendra; Chandra, Naveen; Lingwal, Shashank; Bisht, MPS; Tiwari, Lalit M.
ABSTRACT: The Geospatial extent, availability and threats on Angelica glauca in the alpine region of Western Himalaya were assessed. Landsat-8 data was used to delineate the extent of species using ground control points (GCPs) collected based on the rapid mapping exercise (RME) (4 plots at every 50 m distance, total 40 plots in one transect) as well as herbarium and published literature. To assess the threats on the species, information on livestock population, grazing period, and exploitation by humans were collected. The suitable habitat for A. glauca was recorded ~332 km 2 in the alpine region of Uttarakhand where the species ranged between 0.5 to 1.5 individual m −2 . However, field-based investigations assessed ~ 322 km 2 area as available for the persistence of species in the region. Livestock grazing, collection by human beings for personal and commercial use across the landscape were the major threats for this species.